2016
DOI: 10.1501/vetfak_0000002707
|View full text |Cite
|
Sign up to set email alerts
|

Besi sığırı rasyonlarına maya kültürü ilavesinin besi performansı ile bazı rumen ve kan parametreleri üzerine etkisi

Abstract: Özet: Araştırmada 5-6 aylık yaşta, ortalama 270 kg canlı ağırlığında 16 adet erkek Holştayn ırkı besi sığırı kullanılmıştır. Her birinde sekiz adet hayvan bulunacak şekilde kontrol ve maya grubu olmak üzere iki gruba ayrılmış ve bireysel bölmelerde barındı-rılmışlardır. Hayvanlar fabrika yemi, arpa, pamuk tohumu küspesi ve saman ile beslenmişlerdir. Maya grubu rasyonuna günlük 50 gram canlı maya kültürü (Saccharomyces cerevisiae, 1,4 X 10 8 cfu/g) ilavesi yapılmıştır. Bu çalışma, 15 gün alıştırma, 120 gün dene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Probiotics were also reported to enhance digestion and FCR and improve BWG in young ruminants (Robinson, 2002). Moreover, BWG value increased with the use of Saccharomyces cerevisiae in cattle diets, whereas the final BWG and average BWG were not affected (Gümüş & Şehu, 2016). Alhidary et al (2016) reported that direct-fed microbial supplementation in grazing Awassi lambs had a positive impact on BWG, whereas Saleem et al (2017) stated that the effect of probiotic additive on BW and BWG in the preweaning period was not significant.…”
Section: Resultsmentioning
confidence: 99%
“…Probiotics were also reported to enhance digestion and FCR and improve BWG in young ruminants (Robinson, 2002). Moreover, BWG value increased with the use of Saccharomyces cerevisiae in cattle diets, whereas the final BWG and average BWG were not affected (Gümüş & Şehu, 2016). Alhidary et al (2016) reported that direct-fed microbial supplementation in grazing Awassi lambs had a positive impact on BWG, whereas Saleem et al (2017) stated that the effect of probiotic additive on BW and BWG in the preweaning period was not significant.…”
Section: Resultsmentioning
confidence: 99%